PENGARUH PENGGUNAAN MODEL PEMBELAJARAN MIND MAPPING DAN KECERDASAN SPASIAL TERHADAP HASIL BELAJAR SEJARAH INDONESIA - Muniroh Na; Fahri Yasin (Akademika, 2018)
The influence of the use of mind mapping learning model and spatial intelligence on the leaning outcomes of Indonesian history. This study aims to examine the differences in Indonesian historical learning using mind mapping learning model is superior to the lecture learning model, This research is using experimental method. The target population of all students of class X SMK Kary Guna Bhakti 1 in the city of Bekasi. Samples taken with multi stage random sampling technique. With this technique, two classes were taken for researchactivities, namely class 10C as experimental class and 10A as control class, from each class of 36 students. Techniques of data retrieval analysis using descriptive and inferential analysis of two-track ANAVA to test the hypothesis followed by Tukey or Schffe test. Testing of statistic prerequisite includes testing normality with kolmogorof smirnof and homogeneity testing using anova one way. The results of statistical tests show that the data of the three variables are normal and homogeneous. The results show that: first, the difference oflearning history of Indonesia by using mind mapping learning model is more superior than lecture learning model. Second, there is the influence of learning model interaction with spatial intelligence to the learning result of Indonesian history. Thirdly, there are differences in Indonesian historical learning outcomes between groups of students with high spatial intelligence superior to those with low spatial intelligence. The conclusion of this research is the use of mind mapping learning model is superior compared to the learning model of students who have high spatial intelligence and the interaction between the learning modelwith keverdasan spsasila tinggigi in improving the outcomes of Indonesian history